An empirical study on the factors that triggering retaliatory consumption behaviour of consumers after the deconfinement of movement control order (MCO) in Malaysia - Yap, Woon Seng (2022)
Retaliatory consumption has been discovered after the post pandemic of COVID19 and deconfinement of MCO in Malaysia, consumer’s buying behaviour started to change from rational consumption to irrational consumption as well as revenge buying. The objective of constructing this research is to determine the potential factor that trigger consumer towards retaliatory consumption behaviour. Reactance Theory was applied as the theoretical background of this research to investigate the consumers reaction in respond to the context of consumption freedom were restricted and threatened by certain consumption regulation. Based on the theoretical framework, desire sensation, herd consumption, added purchasing power and influence of social media will be considered as the stimulus factor that affect consumers towards retaliatory consumption behaviour. While survey questionnaire was developed through Google Form and distributed to 300 respondents who have experience in shopping activities after the post-pandemic and lockdown. The collected data from the respondents were used to analyse the hypotheses of this research and interpreted by utilize the IBM SPSS Statistic software. For instance, the result of hypotheses was shows the hypothesis of desire sensation, herd consumption and influence of social media are supported, but only the added purchasing power hypothesis is not supported. Also, findings, theoretical and managerial implications were proposed to highlight the references for experimental method which used to assist future researcher, academic or marketers to have a comprehensively understand the concept and motive of “Retaliatory Consumption Behaviour”.